2020
DOI: 10.1002/chem.202003469
|View full text |Cite
|
Sign up to set email alerts
|

Use of Crown Ether Functions as Secondary Coordination Spheres for the Manipulation of Ligand–Metal Intramolecular Electron Transfer in Copper–Guanidine Complexes

Abstract: Intramolecular electron transfer (IET) between a redox‐active organic ligand and a metal in a complex is of fundamental interest and used in a variety of applications. In this work it is demonstrated that secondary coordination sphere motifs can be applied to trigger a radical change in the electronic structure of copper complexes with a redox‐active guanidine ligand through ligand–metal IET. Hence, crown ether functions attached to the ligand allow the manipulation of the degree of IET between the guanidine l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 74 publications
(82 reference statements)
0
17
0
1
Order By: Relevance
“…Such redox valence tautomerism has been previously reported for N and O based ligands in molecular compounds. 33–35 The carbonaceous support offers a high amount of N moieties where Cu II /Cu I centers can interact with the support. Such stabilization would imply electron withdrawal from N functionalities.…”
Section: Resultsmentioning
confidence: 99%
“…Such redox valence tautomerism has been previously reported for N and O based ligands in molecular compounds. 33–35 The carbonaceous support offers a high amount of N moieties where Cu II /Cu I centers can interact with the support. Such stabilization would imply electron withdrawal from N functionalities.…”
Section: Resultsmentioning
confidence: 99%
“…In 2021, Himmel and co-workers prepared a redox-active bis(guanidine) ligand having a peripheral crown ether group and studied its reversible intramolecular electron transfer (IET) reactivity (Scheme 33). 75 In polar solvent, metal encapsulation induced a large structural change associated with a copper(I) radical ligand undergoing IET to give a Cu(II) species with a closed-shell ligand. Remarkably, these results suggest that the SCS can dictate the spin localization within a coordination complex, hinting at future applications in tunable reactivity.…”
Section: A Bis(guanidine) Ligandmentioning
confidence: 99%
“…Although these extensive studies on Co-oxolene complexes greatly expanded our knowledge about the fundamentals of IET processes and disclosed av ariety of different potential applications,there is still ahigh demand for studies in this field regarding both the fundamental understanding and the development of applications.F urther redox-active ligand classes have to be included into this research theme.In the last years,our group established redox-active guanidines, comprising guanidino-functionalized aromatics (GFAs), as an ew class of versatile redox-active ligands [33][34][35] and intensively studied IET in copper complexes with GFAligands.We showed that IET could be triggered thermally (thermal equilibrium between two redox isomers (VT)), [36][37][38][39] by redox reactions (redox-induced electron transfer (RIET)), [38] by coligand addition [40,41] or substitution, [42] and by metal coordination to as econdary coordination sphere. [43] Moreover, copper complexes with redox-active guanidine ligands were applied in catalytic aerobic phenol homo-and cross-coupling reactions, [44] achieving asignificant improvement of reactivity and selectivity.…”
Section: Introductionmentioning
confidence: 99%